Year of the locust : a soldier's diary and the erasure of Palestine's Ottoman past - Tamārī, Salīm (Berkeley : University of California Press, 2011)
This text captures the end of the Ottoman world and a pivotal moment in Palestinian history. In the diaries of Ihsan Hasan al-Turjman (1893-1917), the first ordinary recruit to describe the World War I from the Arab side, we follow the misadventures of an Ottoman soldier stationed in Jerusalem.
The Erasure of Ottoman Palestine -- The Diary of Ihsan Turjman.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Turjman, Ihsan Hasan, -- 1893-1917 -- Diaries; Turkey. -- Ordu -- History -- World War, 1914-1918.; Turjman, Ihsan Hasan, -- 1893-1917; Turkey. -- Ordu; Turjman, Ihsan Hasan, -- 1893-1917.; World War, 1914-1918 -- Palestine; World War, 1914-1918 -- Jerusalem; World War, 1914-1918 -- Campaigns -- Middle East; World War, 1914-1918 -- Personal narratives, Turkish; Soldiers -- Jerusalem -- Diaries; Turks -- Jerusalem -- Diaries; Jerusalem -- History, Military -- 20th century; Jerusalem -- Social conditions -- 20th century; Guerre mondiale, 1914-1918 -- Palestine; Guerre mondiale, 1914-1918 -- Jérusalem.; Turcs -- Jérusalem -- Journaux intimes; HISTORY -- Military -- World War I; HISTORY -- Middle East -- General; Military campaigns; Social conditions; Soldiers; Turks; Middle East; Middle East -- Jerusalem; Middle East -- Palestine; 1900-1999; Diaries; History; Military history; Personal narratives -- Turkish